The Effectiveness of Fingerprint Attendance Implementation Against Employee Discipline of PT. Gapura Angkasa International Airport at Yogyakarta Airport - Galang Gunabangsa; Yuniar Istiyani (Jurnal Kewarganegaraan, 2022)
AbstractTechnological developments in the era of globalization are increasingly sophisticated, making it easier for all people to access information. One of them is the application of the Automatic Fingerprint Identification System Attendance, which is a tool that really helps employees in attendance. In this research, it is useful to make effective use of fingerprint attendance so that it is easy for a company to control employee attendance. This study uses quantitative methods with the population in this study are all employees of PT. Gapura Angkasa at YIA Airport, while the sample in this study was 30 people which was defined as a research method based on the philosophy of positivism, used to examine certain populations or samples, sampling techniques were generally carried out randomly, data collection using research instrument, data analysis is quantitative or statistical in nature with the aim of testing the established hypothesis. The results of this study based on the t-test in this study resulted in a significant value of 0.000 which is smaller than 0.05 and has a t-count value of 9.254 which is greater than t-table 1.701, which means that the variable x effectiveness of fingerprint attendance affects the variable y of the discipline of PT Gapura Angkasa employees. The magnitude of the effect given from the variable x is 0.754 as evidenced by the value of R square which is 0.754 which is equal to 75.4%. other variables that are not included in this research variable.Keywords: Effectiveness, Fingerprint, Discipline